The Influence of Ship's Seaworthiness and Compensation System Towards Ship's Crew Job Satisfaction" at PT. Humpuss Bulk Transportation Jakarta - Sumali, Banbang; Barasa, Larsen; Gunawan, April (International Review of Management and Marketing, 2019)
The purpose of this study was to determine the influence of ship's seaworthiness and compensation system towards ship's crew job satisfaction at PT. Humpuss Bulk Transportation Jakarta. The populations in this study were seafarers at PT Humpuss Bulk Transportation - Jakarta. The research method used in this study was descriptive and explanatory survey methods with a sample of 20 respondents. Data analysis was performed using SPSS version 25. Based on the results of the study, the size of the contribution of ship's seaworthiness to the crew's job satisfaction at PT. Humpuss Bulk Transportation is 63.1% while the remaining 36.9% is influenced by other factors. The first hypothesis in this study examines whether the ship's seaworthiness partially affects to the job satisfaction of the crew. The results of this study indicate that the ship's seaworthiness has a positive effect on crew job satisfaction. The second hypothesis in this study examines whether the compensation system partially affects the job satisfaction of the crew. The results of this study indicate that the compensation system has a positive effect on crew job satisfaction, so the second hypothesis is accepted. The ship's seaworthiness variable and compensation system together have a positive effect on the crew's job satisfaction. The ship's seaworthiness and compensation system has a positive effect to the ship crew job satisfaction, so the third hypothesis is accepted. Keywords: ship's seaworthiness, compensation system, job satisfaction JEL Classifications: L62, R41, R42 DOI: https://doi.org/10.32479/irmm.8534